1986
DOI: 10.2466/pr0.1986.58.3.705
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Visiting Hospitalized Old People: Sex Differences

Abstract: Old people in religiously affiliated nursing homes were more likely to have visitors than those in secular homes. Women outnumbered men visitors 2:1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Thus, De Young (1985 concluded that an austere and moderate lifestyle was positively related to glass and paper recycling. In the same way, Lievers et al (1986) proved that people with conservative and religious values and lifestyles liked to contribute actively to the society improvement. Dunlap and Van Liere (1986) also found that liberal values were related to a major concern and worry about the environment.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Thus, De Young (1985 concluded that an austere and moderate lifestyle was positively related to glass and paper recycling. In the same way, Lievers et al (1986) proved that people with conservative and religious values and lifestyles liked to contribute actively to the society improvement. Dunlap and Van Liere (1986) also found that liberal values were related to a major concern and worry about the environment.…”
Section: Literature Reviewmentioning
confidence: 86%
“…De Young (1985,1986) concluded that an austere and moderate lifestyle was positively related to glass and paper recycling (McCarty, 1993). In the same way, Lievers et al (1986) proved that people with conservative and religious values and lifestyles liked to contribute actively to the society improvement (Li and Cai, 2012). These authors found strong relationships between universal values and lifestyles and the adoption of sustainable behavior patterns (Fraj and Martinez, 2006).…”
Section: Ecological and Lifestyle Studiesmentioning
confidence: 91%
“…The former was positively correlated with the attitude of ecological consumption, while the latter was negatively correlated with the attitude of ecological consumption. Lievers et al, (1986) argued that people who adhere to traditional values and maintain a simple lifestyle were more likely to engage in social environmental activities [20]. Dunlap and Van Liere (1986) also found that people with liberal values were more concerned about environmental issues [21].…”
Section: Personal Valuesmentioning
confidence: 99%